ChronoPress - Korpus Tekstów Prasowych - Pawłowski, Adam
The resource is a corpus of texts containing a representative sample of the language of the Polish press from the communist period. The segments are annotated with metainformation including the title of the periodical, the title of the article, author, date, style, and distribution. The words in the text are annotated on a morphological and semantic level (basic categories). The corpus includes tools which allow for sample searching, generating time series, concordances, word profiles, and frequency lists. Furthermore, the application offers usage scenarios and explanations of basic concepts or terms. The NLP tools integrated with the application have been prepared in collaboration with the CLARIN-PL consortium.
Keywords: korpus tekstów; prasa PRL; lingwistyka korpusowa; PRL; język prasy; kulturomika